Advents in the Diagnosis and Management of Ischemic Colitis - Misiakos, Evangelos P.; Tsapralis, Dimitrios; Karatzas, Theodore; Lidoriki, Irene; Schizas, Dimitrios; Sfyroeras, George S.; Moulakakis, Konstantinos G.; Konstantos, Chrysostomos; Machairas, Anastasios (Frontiers in Surgery, 2017)
Background. Ischemic colitis (IC) is a common type of ischemic insult, resulting from decreased arterial blood flow to the colon. This disease can be caused from either atherosclerotic occlusive vascular disease or nonocclusive disease. The aim of this study is to present the diagnostic methodology and management of this severe disease based on current literature. Methods. A literature search has been done including articles referring to modern diagnosis and management of IC. Results IC is usually a transient disease, but it can also cause gangrene of the colon, requiring emergency surgical exploration. Diagnosis is troublesome and is based on imaging examinations, mainly computerized tomography, which in association with colonoscopy can delineate the distribution pattern and severity of disease. Conclusion The majority of patients with mild disease have usually complete clinical recovery within a short period. The severe forms of the disease carry high morbidity and mortality rates and prompt surgical intervention is the only way to improve the associated severe prognosis.